The determinants of credit default swap spreads in emerging market economies - Matakane, Lwazi (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2017)
Emerging markets have become a destination for international portfolio flows as a result of global financial integration. This has allowed exogenous factors like sentiment and developed country monetary policy to affect developing countries capital markets and macroeconomic fundamentals. This study analyses the impact of investor sentiment alongside US monetary policy, country specific risks, inflation and domestic stock returns on the BRICS credit default spreads. To investigate this relationship, the study uses panel data and a fixed effects model. The results of the panel regressions suggest that all variables had an impact on the variation of BRICS credit default spreads however the crisis may have distorted the relationship among the variables. Sovereign ratings had an inverse relationship depicting a rise in ratings decreasing the credit default premium. This was in line with a priori expectations. Domestic company earnings also had an inverse relationship with BRCIS credit default premia, the magnitude of which is dependent on the value of the index. This is to say the higher the index, the more significant the effect on the BRICS default premium. US monetary policy was significant and in line with expectations of a linear relationship between emerging market credit default spreads when controlling for the crisis. In the crisis period however, results depicted an inverse relationship going against a priori expectations. The inflation variable was found to have a greater impact on CDS spreads during the crisis period, while the VIX index had a linear relationship with the default premia albeit the impact was not highly significant. The study concludes that the financial crisis was an important event that affected the relationship of these variables with BRICS country default spreads and had read through to market participant's behaviour at the time.
Keywords: Bank loans -- BRIC countries; Risk management -- BRIC countries; Swaps (Finance) -- BRIC countries; BRIC countries -- Economic conditions; Rating agencies (Finance)